2020
DOI: 10.1007/s12144-020-00766-5
|View full text |Cite
|
Sign up to set email alerts
|

Sense of coherence and burnout among school psychologists: The moderating role of loneliness

Abstract: School psychologist have been considered at a high risk for developing work burnout due to their multiple responsibilities, overload and engagement in caring for children, families and professionals. In line with the salutogenic approach, the aim of the current research was to investigate protective and risk factors to burnout. Research has indicated that sense of coherence (SOC) may act as a protective factor. Studies reported that loneliness has been found a risk factor that may advance burnout. The current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Several studies have pointed to the importance of loneliness for entrepreneurs (Akande, 1994;Gumpert & Boyd, 1984), while others have linked loneliness with health (House et al, 1988) and burnout (George-Levi et al, 2020) for the general population. Specifically, Fernet et al (2016) showed the negative link between loneliness in the workplace and the risks of burnout for entrepreneurs.…”
Section: Controlsmentioning
confidence: 99%
“…Several studies have pointed to the importance of loneliness for entrepreneurs (Akande, 1994;Gumpert & Boyd, 1984), while others have linked loneliness with health (House et al, 1988) and burnout (George-Levi et al, 2020) for the general population. Specifically, Fernet et al (2016) showed the negative link between loneliness in the workplace and the risks of burnout for entrepreneurs.…”
Section: Controlsmentioning
confidence: 99%
“…The “professional supervision,” seen as necessary by some social workers, as a moment of reflection and professional and emotional support, is perceived as a “challenge” as it is not present in all services. However, the supervision tool would allow to address some of the critical issues (Matyushkina, 2019; Rae et al, 2017) highlighted by social workers such as “overwork,” “lack of competence,” and a “sense of abandonment,” which in the literature are considered factors that can lead to work burnout (George-Levi et al, 2020; Joaquim et al, 2018). Indeed, according to Robinson (2013), the professional supervision function, due to the ethically demanding nature of the work and the impact on the health of social workers, improves support for those who work in particular with asylum seekers and refugees.…”
Section: Discussionmentioning
confidence: 99%
“…School psychologists have been found to be at risk for developing burnout due to multiple responsibilities, work overload, engagement in caring for others, and shortages of practitioners (George-Levi et al, 2020;Schilling & Randolph, 2020). It can be considered quite alarming, albeit not very surprising, that many practitioners in the field experience less-than-ideal working conditions like lack of support from their nearest superior and high work demands also affecting behavior after work hours.…”
Section: Working Conditionsmentioning
confidence: 99%